PENGGUNAAN ARANG KAYU DAN ARANG BATOK KELAPA TERHADAP KUALITAS ORGANOLEPTIK, KADAR AIR, KETENGIKAN DAN KADAR LEMAK DEDAK PADI YANG DISIMPAN SELAMA 4 - Arief Budi Sutrisno; Farida Fathul; Rudy Sutrisna (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
The production of rice bran in Indonesia was 4 million ton in 2011. This big potency of rice bran hasn’t been optimally used yet as animal feedstuff, because the rice bran has short storage limit. The rice bran can’t be stored in long time because the fat content of the rice bran experiences the hydrolysis reaction easily that causes rancidity. The hydrolysis reaction happens because the reaction of fat and water content. Therefore, the water content of the rice bran must be decreased to prevent the hydrolysis reaction. The charcoal is hygroscopis, namely can absorb water, so that the use of charcoal in storage expected to be able in decreasing the water content and preventing the the hydrolysis reaction on the fat of the rice bran. This research aims to find out the effect of the use of wood and coconut shell charcoal on the organoleptic quality of colour, smell, texture, the water content, rancidity, and the fat of the rice bran stored for 4 weeks. This research used Completely Randomized Design (CRD) with 3 treatments. Each treatment was replicated 4 times. If the result of variance analysis is significantly different on a variable, so it’s continued by using Least Significant Different (LSD) Test on significant level 5% and 1%. The result showed that the use of the coconut shell charcoal influenced very significantly (p<1%) on the smell, water content, peroxide number of the rice bran stored for 4 weeks. The wood charcoal influenced very significantly (p<1%) on the water content and influenced significantly (p<5%) on the peroxide number. Key Word : peroxide number, rancidity, rice bran,